2011
DOI: 10.15835/nbha3915859
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Genetic Variability and Correlation among the Different Traits in Solanum lycopersicum L.

Abstract: In present study the genetic diversity in some tomato genotypes were investigated in two years at North-west of Iran where due to its geographical situation is one of the most favourable regions for tomato cultivation. Twenty five tomato genotypes were evaluated for yield and important morphological traits during 2006-2007. Experiment was conducted in a 5 lattice square design with 3 replications in each one of years. Data on morphological traits were collected from central row on individual plants basis on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
(10 reference statements)
6
14
0
Order By: Relevance
“…This association shows that the increase in FWidth leads to the increase in FW as well. Bernousi et al (2011) recorded positive significant correlation for FW with FWidth and FL which is in harmony with our results. Islam et al (2010) also estimated positive significant correlation of fruit diameter/width both at genotypic and phenotypic levels with individual FW and yield plant -1 which indicated that as the diameter of fruits increases the individual FW and yield plant -1 would increase.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This association shows that the increase in FWidth leads to the increase in FW as well. Bernousi et al (2011) recorded positive significant correlation for FW with FWidth and FL which is in harmony with our results. Islam et al (2010) also estimated positive significant correlation of fruit diameter/width both at genotypic and phenotypic levels with individual FW and yield plant -1 which indicated that as the diameter of fruits increases the individual FW and yield plant -1 would increase.…”
Section: Discussionsupporting
confidence: 92%
“…Morphological description and classification is a traditional approach to quantify genetic differences, and is often used for genetic diversity analysis (Khadivi-khub et al 2008;Nikoumanesh et al 2011;Terzopoulos & Bebeli 2008;). In tomato, yield is the cumulative effect of many components contributing individually to yield (Bernousi et al 2011). Different characteristics viz.…”
Section: Introductionmentioning
confidence: 99%
“…In strawberry (Fragaria •ananassa), Monma and Takada (1991) found negative correlations between TYLD and both SS and ACID. In tomato (Solanum lycopersicum), Bernousi et al (2011) found weak positive correlations between TYLD and ACID and SS, and Ramana et al (2007) found ACID and SS were not significantly correlated with TYLD. Our results are similar to those of Rakonjac (2006), who found a positive genetic correlation between TYLD and SS and a negative correlation between TYLD and ACID content in peach (Prunus persica).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative traits have been previously used for similar studies in tomato. As for example, Henareh et al (2015) studied 21 quantitative traits in 97 tomato accessions from Iran and Turkey, Bernousi et al (2011) surveyed 25 tomato genotypes with the help of 19 morphological traits; Bhattarai et al (2016) analyzed 71 tomato genotypes with 8 morphological traits. All these studies revealed significant variation among the studied genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The use of morphological markers and agronomic traits has been extensively applied in studying genetic variation in plants. Compared to molecular markers and biochemical methods, morphological markers are very easy, more direct and less costly (Bernousi, 2011). Estimation of genetic diversity in tomato has been carried out by many researchers in the world using morphological approaches (Hu et al, 2012;Chernet et al, 2014;Osekita and Ademiluyi, 2014;Sacco et al, 2015).…”
Section: Introductionmentioning
confidence: 99%